Intravascular Ultrasound‐Guided Primary Percutaneous Coronary Intervention With Drug‐Eluting Stent Implantation in Patients With ST‐Segment Elevation Myocardial Infarction - Youn, Young Jin (Clin Cardiol, 2011)
BACKGROUND: Studies investigating the clinical outcome of intravascular ultrasound (IVUS)‐guided primary percutaneous coronary intervention (PPCI) in patients with ST‐segment elevation myocardial infarction (STEMI) show conflicting results. The aim of our study was to evaluate whether IVUS‐guidedPPCI with drug‐eluting stents (DESs) in STEMI patients improves clinical outcome. HYPOTHESIS: IVUS‐guided PPCI is superior to angio‐guided PPCI. METHODS: Three hundred forty‐one patients who underwent PPCI for STEMI and survived the hospitalization were enrolled in this study. Two hundred sixteen (63.3%) patients were treated with angio‐guided PPCI and 125 (36.7%) patients were treated with IVUS‐guided PPCI. The primary endpoint was defined as the composite of death, myocardial infarction, target vessel revascularization, and target lesion revascularization at the 3‐year follow‐up visit. RESULTS: Male gender, dyslipidemia, and smoking were frequent in the IVUS‐guided PPCI group. These patients had a higher rate of radial approach, adjunctive ballooning, thrombectomy, and the use of a glycoprotein IIb/IIIa inhibitor. The number and length of implanted stents were higher in the IVUS‐guided PPCI group. The primary end point (18.1% vs 12.8%, P = 0.22) and stent thrombosis (2.8% vs 2.4%, P = 1.00) was not different between the groups. CONCLUSIONS: In our observational study, IVUS‐guided PPCI with DESs in patients with STEMI did not improve clinical outcome or stent thrombosis. © 2011 Wiley Periodicals, Inc. The authors have no funding, financial relationships, or conflicts of interest to disclose.